Linkages Perekonomian Bali - Rizky Zulkarnain; Nasiyatul Ulfah (Politeknik Statistika STIS, 2021)
Several studies have been conducted to analyze multiplier effect of Bali economy. However, those studies merely focus on intersectoral linkages using Input-Output (IO) model, whereas regional production activities could be interdependent through various externalities and supply-chain networks. This study aims to analyze Bali economy by considering interregional linkage as well as intersectoral linkage. This study employs Inter Regional Input Output (IRIO) model. The IRIO table (17 industries x 34 provinces) was acquired from Statistics Indonesia (BPS). The results showed that there were several key sectors in Bali economy: Electricity and Gas, Transportation and Storage, Information and Communication, and Business Activities. Electricity and Gas had highest intersectoral linkage and output multiplier. Moreover, interregional analysis showed that final demand shock in Bali had significant impact to provinces in Java, especially East Java. On the other side, Bali economy was influenced by final demand shock in West Nusa Tenggara.